Survival impact and predictive factors of axillary recurrence after sentinel biopsy. (May 2016) - Houvenaeghel, Gilles; Classe, Jean Marc; Garbay, Jean-Rémy; Giard, Sylvie; Cohen, Monique; Faure, Chistine; Charytansky, Hélène; Rouzier, Roman; Daraï, Emile; Hudry, Delphine; Azuar, Pierre; Villet, Richard; et al.
Abstract: Background: The rate of axillary recurrence (AR) after sentinel lymph node biopsy is usually low but few studies investigated its impact on survival. Our aim was to determine the rate and predictive factors of AR in a large cohort of breast cancer patients and its impact on survival. Patients and methods: From 1999 to 2013, 14, 095 patients who underwent surgery for clinically N0 previously untreated breast cancer and had sentinel lymph node biopsy were analysed. A simplified score predictive of AR was established. Results: Median follow-up was 55.2 months. AR was observed in 0.51% of cases, with a median time to onset of 43.4 months. In multivariate analysis, the occurrence of AR was significantly correlated with grade 2 or 3 disease, absence of radiotherapy and tumour subtype (hormonal receptor [HR]– / human estrogen receptor [HER]+). AR rates were 1% for triple-negative tumours, 2.8% for HER2-positive tumours, 0.4% for luminal A tumours, 0.9% for HER2-negative luminal B tumours, and 0.5% for HER2-positive luminal B tumours. A simplified score predictive of the occurrence of AR was established. Patients could be divided into three different score groups (p < 0.0001). In multivariate analysis, overall survival was significantly lower in cases of AR (p < 0.0001), age >50, lymphovascular invasion, grade 3 disease, sentinel node (SN) macrometastases, tumour size >20 mm, absence of chemotherapy and triple-negative phenotype. Survival in patients with AR was significantly lower in case of early-onset (2 years) AR (p = 0.017). Conclusions: : Isolated AR is more common in Her2-positive/HR-negative triple-negative tumours with a more severe prognosis in triple-negative and Her2-positive/HR-negative tumours, and represents an independent adverse factor justifying an indication for systemic treatment for AR treatment. However, the benefit of any systemic treatment remains to be proven. Highlights: Among 14, 095 patients, axillary recurrence (AR) rate was 0.51%. A score predictive of AR occurrence was established with three different groups. Isolated AR is more common in triple-negative and HER2 tumors. AR represents an independent adverse factor. Survival in patients with AR was significantly lower in case of early-onset AR.